mTOR Signaling: A Central Pathway to Pathogenesis in Systemic Lupus Erythematosus? - Fernandez, David (2010)
Systemic lupus erythematosus (SLE) is a common autoimmune disease with unclear etiology. Treatments for it often provide inadequate control of disease activity or are limited by side effects. Recent studies have shown that rapamycin can be an effective treatment in both murine lupus models and human SLE. We demonstrated that rapamycin could directly alter molecular abnormalities in SLE T cells related to calcium signaling but not mitochondrial function. However, in light of increased knowledge of the role of mammalian target of rapamycin (mTOR) signaling throughout the immune system, several other potential sites of rapamycin action have been revealed. Specifically, mTOR regulates the production of interferon-α and the maintenance of immune tolerance at the level of the regulatory T cell and the dendritic cell, and can promote Th2 versus Th1 immune responses. Thus mTOR offers a window into diverse facets of lupus pathogenesis as well as a unifying narrative in our understanding of the therapeutic efficacy of rapamycin in SLE.